Identification and characterization of Brevibacillus halotolerans B-4359: a potential antagonistic bacterium against red pepper anthracnose in Korea - Kim, Heejin; Lee, Younmi; Hwang, Ye-Ji; Lee, Mi-Hwa; Balaraju, Kotnala; Jeon, Yongho (Frontiers in Microbiology, 2023)
Our study aimed to identify potential biocontrol agents (BCAs) against major phytopathogens under in vitro conditions by screening the Freshwater Bioresources Culture Collection (FBCC), Korea. Of the identified 856 strains, only 65 exhibited antagonistic activity, among which only one representative isolate, Brevibacillus halotolerans B-4359 was selected based on its in vitro antagonistic activity and enzyme production. Cell-free culture filtrate (CF) and volatile organic compounds (VOCs) of B-4359 were shown to be effective against the mycelial growth of Colletotrichum acutatum. Notably, B-4359 was found to promote spore germination in C. acutatum instead of exhibiting a suppressive effect when the bacterial suspension was mixed with the spore suspension of C. acutatum. However, B-4359 showed an excellent biological control effect on the anthracnose of red pepper fruits. Compared to other treatments and untreated control, B-4359 played a more effective role in controlling anthracnose disease under field conditions. The strain was identified as B. halotolerans using BIOLOG and 16S rDNA sequencing analyses. The genetic mechanism underlying the biocontrol traits of B-4359 was characterised using the whole-genome sequence of B-4359, which was closely compared with related strains. The whole-genome sequence of B-4359 consisted of 5,761,776 bp with a GC content of 41.0%, including 5,118 coding sequences, 117 tRNA, and 36 rRNA genes. The genomic analysis identified 23 putative secondary metabolite biosynthetic gene clusters. Our results provide a deep understanding of B-4359 as an effective biocontrol agent against red pepper anthracnose for sustainable agriculture.